Pengaruh Kombinasi Daun Katuk dan Daun Kacang Panjang terhadap Produksi ASI: The Effect Of The Combination of Katuk Leaf and Leather of Bean Long on Breast Milk Production - Fajrin, Dessy Hidayati; Desy Rosita; Surtalia Nainggolan (Indonesian Journal of Midwifery (IJM), 2023)
Exclusive breastfeeding (ASI), according to the World Health Organization, so pregnant women and mothers who have just given birth are informed about the benefits and advantages of breastfeeding, where it is the best nutrition and protection against disease. Exclusive breastfeeding coverage in the working area of the Lumar District Health Center, Bengkayang Regency, has not been achieved. Lack of nutrition causes significant losses for babies, especially growth and development problems that can experience stunting. Vegetables that can increase the volume of breast milk include katuk leaves and long bean leaves. This study aimed to find out how "The Effect of the Combination of Katuk Leaves and Long Bean Leaves on Breast Milk Production in the Working Area of the Lumar Health Center, Bengkayang Regency." This research method used quantitative experiments with a quasi-experimental research design with one group pretest and posttest without a control group. This study used a population of 34 people using the total sampling technique. The results of statistical tests using non-parametric tests, namely the Wilcoxon test, showed that the p-value is p = 0.000 (p < 0.05), it could be concluded that there was a significant difference in breast milk production before and after giving a combination of katuk leaves and long bean leaves on breast milk production.   Abstrak Pemberian Air Susu Ibu (ASI) secara Eksklusif menurut World Health Organization agar wanita hamil dan ibu yang baru melahirkan diberitahu manfaat dan keunggulan ASI dimana gizi terbaik serta perlindungan terhadap penyakit. Cakupan ASI Eksklusif di wilayah kerja Puskesmas Kecamatan Lumar Kabupaten Bengkayang belum tercapai. Kekurangan nutrisi menyebabkan kerugian yang cukup signifikan bagi bayi terutama masalah tumbuh kembang dapat mengalami stunting. Sayuran yang dapat meningkatkan volume ASI diantaranya adalah daun katuk dan daun kacang panjang. Tujuan penelitian ini untuk mengetahui Bagaimana “Pengaruh Kombinasi Daun Katuk dan Daun Kacang Panjang terhadap Produksi ASI di Wilayah Kerja Puskesmas Lumar Kabupaten Bengkayang”. Metode penelitian ini menggunakan kuantitatif eksperimen dengan desain penelitiannya quasi eksperimen rancangan penelitian adalah “One group pretest- posttest without control grup” Populasi 34 orang dengan menggunakan teknik total sampling . Hasil: Uji statistiknya uji normalitas dengan uji non-parametrik yaitu Uji Wilcoxon menunjukan bahwa p-value bernilai p=0,000 (p<0,05) maka dapat disimpulkan terdapat perbedaan bermakna produksi ASI sebelum dan sesudah pemberian kombinasi daun katuk dan daun kacang panjang terhadap produksi ASI.